PHYSICAL CULTURE IN EDUCATIONAL PRACTICE OF BUKOVYNA IN THE LATE 19TH - EARLY 20TH CENTURIES - Олег Винничук (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The process of physical culture establishment and development in schools of Bukovyna in the late 19th - early 20th centuries has been described. The reasons for and the disadvantages of the physical culture establishment process in the educational policy of Habsburg Monarchy have been determined and characterized. It has been proven that social and political life of the residents of Bukovyna in the second half of the 19th century helped to implement reformation and innovative methods into public schools, which had been already approbated in Western European countries. Basic approaches to the implementation of the content of physical culture of the pupils in Bukovyna in the period being explored have been pointed out.